Numbered Heads Together (Nht) Cooperative Learning Model on Students' Mathematic Problem Solving Ability Study on Class ViII Students of Golden Star Informatics SMP - ria Irawati; Sri Wahyuni (Mathematics Research and Education Journal, 2022)
This research is motivated by the low mathematical problem solving ability of students at the Golden Star Informatics Junior High School. This study aims to determine the effect of the Numbered Heads Together (NHT) cooperative learning model on the mathematical problem solving ability of the students of class VIII SMP Informatika Golden Star. The research method used is quasi-experimental with posttest only control design. Class VIII A as the control class and class VIII B as the experimental class. The instrument used to determine the mathematical problem solving ability is the post test results of six questions. Data analysis for students' mathematical problem solving ability was carried out using the t' test. Based on the results of the data analysis of students' mathematical problem solving abilities, the results of hypothesis testing using the t' test were obtained compared to at a significant level of 0.05 Because , it was rejected. This shows that the average mathematical problem solving ability of students from the two groups is not the same. Then there is the effect of the application of the NHT cooperative learning model on the mathematical problem solving abilities of eighth grade students of Golden Star Informatics Junior High School.